Effect, Performance and Conversion of Plastic to Crude Oil - Dr. Vinod Kumar Biradar (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Plastic was invented by Alexander Parkes in 1860. Plastics have become a crucible part in today’s world. Due to their light weight, durability, design flexibility, they are excessively used in industry as well as household and other fields. The demand for plastic is increasing day by day which now pose a tremendous threat to the environment. The study focus on the design and fabrication of machine to convert plastic into oil as an effort in finding environment-friendly means of waste recycling by means of pyrolysis. It is an alternative solution to increasing problem of waste disposal. Pyrolysis keeps running without oxygen and in high temperature of around 250°C for which reactor is manufactured to give the expected temperature to the response. The waste plastics are subjected to depolymerization, pyrolysis, catalytic cracking and fractional distillation to obtain different value added fuels such as petrol, kerosene, and diesel. Our Project deals with the extraction of oil from the waste plastics termed as plastic pyrolysed oil which can be marketed at much cheaper rates compared to that present in the market. As we know that both Plastics and Petroleum derived fuels are Hydrocarbons that contain the elements of Carbon & Hydrogen. Pyrolysis process becomes an option of waste-to-energy technology to deliver bio-fuel to replace fossil fuel. The advantage of the pyrolysis process is its ability to handle unsort and dirty plastic. The pre-treatment of the material is easy. Plastic is needed to be sorted and dried. Pyrolysis is also nontoxic or non-environmental harmful emission unlike incineration. In this investigation, plastic waste (poly propylene) are utilized for pyrolysis to get fuel oil that has comparable physical properties as the energizes like petroleum, diesel and so on Converting waste plastics into fuel hold great promise for both the environmental and economic scenarios.